Development Of Hydraulic Regenerative Braking Testbench - Mahyuddin, Muhammad Syahir (Universiti Sains Malaysia, 2019)
Hybrid vehicle is a vehicle that operates with the combination of two power sources. The hybrid technology helps reduces the vehicle fuel consumption and gas emissions through the regenerative braking and acceleration assist system. As most of the light duty vehicles are equipped with electric hybrid system, this project focuses on the implementation of hydraulic hybrid system into the light passenger vehicle to study the performance of hydraulic hybrid vehicle (HHV). The test bench for hydraulic hybrid system in parallel-through-the-road architecture is developed which involved the processes of hydraulic configurations selection, designing the control system, the hydraulic circuit layout and test bench CAD model, and analyzing the expected performance of regenerative braking system. The performance analysis comprises of V-belt drive selections for regenerative braking and validation of HHV deceleration rate using drive cycle data. The V-belt selections analysis shows that one V-belt type D can undergo regenerative braking without slip. For deceleration rate analysis, the average deceleration rate of HHV is much higher than that from drive cycle with the difference by 85% while the maximum deceleration rate of HHV have the difference by only 22% from the drive cycle value. Therefore, the modification on the control system is necessary to control the HHV deceleration. With the result of these analyses, the modification and complete fabrication of HHV test bench can be accomplished in future as well as the testing of hydraulic hybrid operation.